PENGARUH TEMPERATUR PERMUKAAN PANEL SURYA TERHADAP KAPASITAS DAYA YANG DIHASILKAN - Ervan Hasan Harun; Fiqry Ahmad; Jumiati Ilham (Program Vokasi-Universitas Negeri Gorontalo, 2023)
Solar panels are a semiconductor component that is capable of converting solar energy into electrical energy through the photovoltaic principle. Fluctuations greatly influence the electrical energy produced by solar panels in surface temperature. Therefore, this research aims to assess the impact of solar panel surface temperature and compare the power produced by two types of solar panels, namely polycrystalline and monocrystalline panels. The method used in this research is direct measurement using a temperature measurement device with an infrared thermometer and a solar power meter. The results of measurements and analysis show that the higher the surface temperature of the solar panel, the less power produced will decrease. In addition, in a comparison of the output power between polycrystal and monocrystal-type solar panels, it was found that the power of the monocrystal type was higher than the polycrystal type.